Loneliness and generalized problematic Internet use : parents’ perceived knowledge of adolescents’ online activities as a moderator - Ang, Rebecca P. (2013)
This study examined adolescents’ perceptions of parents’ knowledge of their online activities as a moderator of the relationship between loneliness and generalized problematic Internet use (PIU). The purpose of this study was to address two gaps in research. First, previous research has only investigated these relationships from a main effects perspective; the present study extended research by examining generalized PIU from an interaction effects perspective. Second, it is timely to examine the relationship between loneliness and generalized PIU in an adolescent sample which has not been previously explored. A total of 1098 adolescents (49.2% male, 50.8% female) from Grade 8 and Grade 9 classes participated in this study. The key finding was that perceived parental knowledge was a moderator of the relationship between loneliness and generalized PIU; parental knowledge was better able to differentiate adolescents’ level of generalized PIU at lower rather than at higher levels of loneliness. This moderator effect was stronger in magnitude for parents who had no awareness of their adolescents’ online activities compared to parents who were in the know about their adolescents’ online activities. These findings emphasize the importance of prevention and early intervention work with early adolescents and their parents with respect to adolescent loneliness and generalized PIU.